Decreased glucose bioavailability and elevated aspartate metabolism in prostate cancer cells undergoing epithelial‐mesenchymal transition. Issue 7 (4th February 2020) - Chen, Yule; Wang, Ke; Liu, Tianjie; Chen, Jiaqi; Lv, Wei; Yang, Wenjie; Xu, Shan; Wang, Xinyang; Li, Lei
Abstract: Prostate cancer (PCa) is a common malignancy with a high tendency for metastasis. Epithelial‐mesenchymal transition (EMT) plays a crucial role in PCa metastasis. Metabolic reprogramming offers metabolic advantages for cancer development and could result in the discovery of novel targets for cancer therapy. However, the metabolic features of PCa cells undergoing EMT remain unclear. We used metabolome and transcriptome analyses and found that PCa cells undergoing EMT showed impaired glucose utilization. In vitro studies demonstrated that PCa cells undergoing EMT were less addicted to glucose than epithelial‐like PCa cells. However, cells that underwent EMT had higher levels of aspartate and its downstream metabolites, indicative of upregulated aspartate metabolism. As aspartate is a contributor for EMT and metastasis in human cancer cells, we conclude that this metabolic reprogramming may play a vital role in EMT and PCa progression. Abstract : The present study preliminarily reveals the metabolic alterations in prostate cancer (PCa) cells during epithelial‐mesenchymal transition (EMT). Mesenchymal PCa cells showed lower glucose bioavailability and glucose addiction than epithelial PCa cells but higher aspartate metabolism. This finding may provide clues for screening new therapeutic targets to prevent PCa metastasis.